The China Soft Power: Confucius Institute in Build Up One Belt One Road Initiative in Indonesia - Sitti Marwah; Ratna Ervina (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2021)
One Belt One Road Initiative which has been running for four years has shown a significant result, but, there are still some small obstacles which may hinder its success, one of them is language gap which is mastering Chinese language also known as Mandarin.  Therefore,   Confucius Institute becomes an international platform to spread Chinese language and culture around the world in order to enhance the understanding of China, has already been established before by the Chinese Ministry of Education. The establishment of Confucius Institute then be aligned to the development of One Belt One Road Initiative which function as an information service, job training and media center that can help establish cooperation between Chinese companies and local companies. Confucius Institute is expected to overcome language barriers that can lead to misunderstandings so as to benefit diplomatic relations between China and countries along the path of One Belt One Road. Through this paper the authors will describe China's soft power through the Confucius Institute and One Belt One Road Initiative in Indonesia and how these two products run to complement each other in order to enhance the charm of China in the eyes of the world. Keywords: China Soft Power, One Belt One Road, Confucius Institute, Indonesia